What difference do polarisation measures make? an application to China - Zhang, Xiaobo; Kanbur, Ravi (Informa UK Limited, 2001)
In recent years there has been much discussion of the difference between inequality and polarisation. The vast literature on inequality is held to miss out key features of distributional change, which are better described as changes in polarisation. Axioms have been proposed which capture some of these differences, and measures of polarisation, as distinct from inequality, have been suggested. The theoretical distinctions proposed in this literature are indeed interesting. But do the newly proposed measures of polarisation give different results in comparing societies over time? We address these questions for China, where dramatic increases in inequality and polarisation have been much discussed in the literature. We find that, contrary to theoretical expectation, the new measures of polarisation do not generate very different results from the standard measures of inequality. The article ends by considering a different approach to polarisation which might better conform to the policy concerns expressed in the specific context of China. -- Authors' Abstract